Review of Food Poisoning Outbreak Investigation Reports in Provinces of the Health Region 5, 2005-2007 - Watcharakorn, Siripon (Journal of Health Science of Thailand, 2018)
Between 2005 and 2007, incidence of food poisoning ranked among the top ten diseases in the reporting system in provinces in the health region 5 (Lop Buri, Sing Buri, Chai Nat, and Sara Buri). The author reviewed food poisoning outbreak investigation reports in the region during this 3 years to determine situation, severity, risk factors and quality of performance and reports. A total of 19 food poisoning outbreak investigations, which were undertaken by 38 districts and/or 4 provincial surveillance and rapid response teams (SRRT), were reported during 2005-2007. The number of reports increased from 3 in 2005 to 9 in 2007. The number of outbreaks peaked in November (26.3%) and commonly found in schools (36.8%), followed by households (31.6%). In each mishap, less than 20 persons were involved in most (63.2%) of the incidents. Meat was the most common incriminated food. Uncooked food contaminated with pathogens or food with toxic chemicals was the main cause of the outbreaks. Salmonella spp. was the pathogen most commonly implicated. Similarity in their causes was noticeable. Descriptive epidemiology was used in most outbreak investigations. Incomplete investigation reports included incorrect case definition, improper use of descriptive statistics, and no epidemic curve. Incomplete report writing often lacked information on mode of transmission, proper discussion, and errors on references. Field training under experienced supervisors may increase SRRT skills. Prevention programs should, therefore, emerge from those fruitful SRRTs investigative reports.